Analisis Faktor-Faktor yang Berpengaruh terhadap Return Saham Perusahaan Jasa di Bursa Efek Indonesia pada Periode 2018-2021 - Giyartiningrum, Eko; Azzahra, Ummi Fajarina; Prasetyo, Heri; Swandari, Fifi (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study aims to explore the impact of DER, LDR, and NIM on stock returns of service companies in the IDX for the period of 2018-2021. Secondary data was obtained purposively for company financial reporting or via the website www.idx.com. Data analysis is done through multiple regression testing, F-test, and t-test. The results obtained show that only DER and LDR partially have a significant effect on stock returns of service companies in the study period, while NIM has proven to have no significant effect on stock returns. Simultaneously, the three independent variables proved to have a significant effect on service company stock returns in the study period. It is expected that the results of this study will contribute to providing deeper insight into the various factors that can influence stock returns in the Indonesian capital market and serve as a reference for investors and financial managers in making investment decisions.